Allergic rhinitis. Modern opportunities of pathogenetic therapy - G. N. Nikiforova; V. M. Svistushkin; A. V. Zolotova (Медицинский совет, 2019)
Allergic rhinitis is a global public health problem at the present stage, given the high prevalence, the formation of therapy-resistant phenotypes, high comorbidity and the negative impact on all aspects of a patient’s life. Histamine is one of the main mediators of allergy, and therefore drugs number one in the treatment of patients with AR of all options are antihistamine drugs or H1-blockers. The innovative antihistamine drug of the second generation levocetirizine (Allerway®) prevents the development and facilitates the course of allergic reactions, also has anti-inflammatory and antiallergic action. Allerway® is bioequivalent to the original drug, has broad indications for use, has established itself as an effective drug with a good safety profile.